Strategi Fundraising Pada Lembaga Amil Zakat Infaq Sedekah Muhammadiyah Kota Batu - Ramadhan, Nauval Hilmy; Hakim, Rahmad; Muslikhati, Muslikhati (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2021)
The purpose of this study is to conduct an in-depth analysis of the LAZISMU fundraising strategy in Batu City. In this research, the researcher uses descriptive qualitative method so that it can describe what kind of fundraising strategy used by LAZISMU Batu City. The conclusion of this study shows that LAZISMU Batu City has two patterns in its fundraising strategy, namely, raising funds through available sources and raising funds by creating new funding sources. Fundraising on available sources by institutions uses methods such as identification of muzakki, use of direct and indirect fundraising methods, safeguarding and management of muzakki, as well as monitoring and evaluation. Raising by creating new funding sources is carried out through PPOB services in the form of bill payment service providers such as water, electricity, wifi, and others.